Ayat Toleransi Dalam Al-Qur’an Perspektif Tafsir Al-Kabir (Mafaatihul Ghaib) - Ahmad Zainul Arifin; Khairuddin Khairuddin; Moh Rifa’i (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2019)
In the millennial era it is very important in describing the lives of interfaith people on the face of the earth. Various social media certainly become a very important tool for each group to convey ideas quoted based on the teachings of their respective religions. The frequent occurrence of trends in values, morals and ethics causes the relationship between religious people to become increasingly span in the field of trust. Various groups from each religion often complained about their achievements in terms of personality and even on political matters so that such a huge impact is vulnerable to minorities in certain regions. This is where the Qur'an plays a very important role as one of the rejects of Muslim thinking. In addition, the Qur'an also plays an important role for all human beings as social beings without exception. Although al-Qu'an himself has stated that to be one does not have to be the same. Different religions, cultures, nationalities or others is not a limiting thing to build a harmony of living together. It's just that, at the present time many thinkers who stand tall are only for their own sake, don't care about what's around them. For this reason, we are writing a study based on events that often occur on the face of the earth. Inserted with some ideas from several figures and an expert in the interpretation of the Qur'an in order for the writer and the reader to understand more deeply what tolerance is or what harmony is religious life